First Report on the Synergistic Interaction between Essential Oils against the Pinewood Nematode Bursaphelenchus xylophilus - Jorge M. S. Faria; Tomás Cavaco; Diogo Gonçalves; Pedro Barbosa; Dora Martins Teixeira; Cristina Moiteiro; Maria L. Inácio (Plants, 2023)
Control of the pinewood nematode (PWN), the causal agent of pine wilt disease, can be achieved through the trunk injection of nematicides; however, many pesticides have been linked to environmental and human health concerns. Essential oils (EOs) are suitable alternatives due to their biodegradability and low toxicity to mammals. These complex mixtures of plant volatiles often display multiple biological activities and synergistic interactions between their compounds. The present work profiled the toxicity of eight EOs against the PWN in comparison to their 1:1 mixtures, to screen for successful synergistic interactions. Additionally, the main compounds of the most synergistic mixtures were characterized for their predicted environmental fate and toxicity to mammals in comparison to emamectin benzoate, a commercial nematicide used against PWN. The mixtures of Cymbopogon citratus with Mentha piperita and of Foeniculum vulgare with Satureja montana EOs showed the highest activities, with half-maximal effective concentrations (EC50) of 0.09 and 0.05 µL/mL, respectively. For these, complete PWN mortality was reached after only ca. 15 min or 2 h of direct contact, respectively. Their major compounds had a higher predicted affinity to air and water environmental compartments and are reported to have very low toxicity to mammals, with low acute oral and dermal toxicities. In comparison, emamectin benzoate showed lower nematicidal activity, a higher affinity to the soil and sediments environmental compartments and higher reported oral and dermal toxicity to mammals. Overall, uncovering synergistic activities in combinations of EOs from plants of different families may prove to be a source of biopesticides with optimized toxicity against PWNs.